Oberoende förvaltning av privatägd skog i Härjedalen – finns det intresse för det? - Bäckman, Manne (SLU/School for Forest Management, 2016)
This study investigates the interest among private forest owners to have their forest managed by an independent forest consultant.The objective is to assess the market potential for consultancy services in forest management. The survey was conducted in the province of Härjedalen, Sweden, through telephone interviews with 21 private forest owners. Most of the forest owners were interested in independent forest management.